Association between low ankle-brachial index and accelerometer-derived sedentary and exercise time in the asymptomatic general population. (August 2015) - Kulinski, Jacquelyn P; Sanghavi, Monika; Ayers, Colby R; Das, Sandeep R; Banerjee, Subhash; Berry, Jarett D; Addo, Tayo; De Lemos, James A; Kumbhani, Dharam J
Sedentary behavior is an adverse health risk factor that is independent of physical activity. The relationship between sedentary behavior, exercise activity and the ankle-brachial index (ABI) is not well understood. We analyzed data from the National Health and Nutrition Examination Survey (NHANES) 2003–2004. Accelerometer data were used to quantify exercise and sedentary time for each participant. A low ABI was defined as a value <1.0 (including borderline values). Multi-variable adjusted logistic regression analyses were performed with sedentary and exercise times as independent variables, adjusting for important confounders. There were 1443 asymptomatic participants (mean age 61 years, 49% female, 55% current/prior smokers) with mean daily sedentary and exercise times of 454±144 and 18±20 minutes, respectively. Of the participants, 23% had an ABI <1.0 (8.7% with ABI <0.9). Sedentary time was positively associated with a low ABI (odds ratio [OR] 1.22 per 1 standard deviation [SD], [95% confidence interval (CI), 1.03–1.43]; p =0.02) while exercise time was inversely associated with a low ABI (OR 0.71 per 1 SD, [95% CI, 0.57–0.89]; p =0.003). Sedentary time is associated with low ABI values in the asymptomatic population. This association appears to be independent of exercise time and warrants further investigation.